2017
DOI: 10.1186/s13014-017-0779-y
|View full text |Cite
|
Sign up to set email alerts
|

Timing of thoracic radiotherapy in the treatment of extensive-stage small-cell lung cancer: important or not?

Abstract: BackgroundThis study evaluated the prognosis of patients with extensive-stage small-cell lung cancer (ES-SCLC) that may be associated with timing of thoracic radiotherapy (TRT).MethodsES-SCLC patients (n = 232) without progression were retrospectively analyzed after first-line induction chemotherapy. Patients in the TRT group were stratified as early-TRT (ERT; ≤3 cycles of induction chemotherapy received prior to TRT, n = 65) or late-TRT (LRT; >3 cycles, n = 122). To avoid selection bias, we conducted Propensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…More in-depth research should be made to work out to further explain therapeutic schedule about liver metastasis of ES-SCLC. Two previously studies by Nakazawa K et al and Ren Y et al revealed that single metastasis was associated with better OS compared with multiple ones [33,34].Contrastingly, metastasis site (multiple vs single) as well as number of metastasis were signi cantly obvious in univariate analysis ,while they did not affect the survival time in multivariate analysis, which was consistent with a published study by Luo J et al [23]. One possible reason was the difference in sample size between the two groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More in-depth research should be made to work out to further explain therapeutic schedule about liver metastasis of ES-SCLC. Two previously studies by Nakazawa K et al and Ren Y et al revealed that single metastasis was associated with better OS compared with multiple ones [33,34].Contrastingly, metastasis site (multiple vs single) as well as number of metastasis were signi cantly obvious in univariate analysis ,while they did not affect the survival time in multivariate analysis, which was consistent with a published study by Luo J et al [23]. One possible reason was the difference in sample size between the two groups.…”
Section: Discussionsupporting
confidence: 89%
“…A retrospective study by Luo et al indicated that early TRT did not show signi cant bene t over late TRT [23]. Based on the study, we evaluated the e cacy of introducing TRT at different points.…”
Section: Discussionmentioning
confidence: 99%
“…We defined ED-SCLC polymetastases as more than or equal to two organ metastases and oligometastases as less than one organ metastasis. This SCLC categorization method was also described recently by Jeremic et al and Luo et al 3 , 20 …”
Section: Methodsmentioning
confidence: 93%
“…In RTOG 0937 trial and one retrospective Chinese study also no difference was found in survival for patients who received RT early or late. 9 , 25 On the contrary, meta-analysis for limited SCLC, showed that earlier or shorter RT brings 7.7% advantage in 5-year survival. 26 …”
Section: Discussionmentioning
confidence: 99%